Science Concepts in Early Childhood Education - Nurkholisoh, Diah (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The concept of science in early childhood programs is an abstraction that represents objects, events, activities or relationships that have the same sign that is related to scientific knowledge (science). This concept is oriented to the process of recognition and mastery process about scientific material that is appropriate to the age level. Includes facts, theories, concepts, principles, laws, terms, processes and problem solving. Therefore, the realm of science for early childhood includes two study points namely the first, the contents of the study material and the second field of development or ability to be achieved. To achieve the concept of science as a whole, requires the efforts and competence of teachers in loading aspects of the nature of science in the learning process. One of the main factors is the low understanding of teachers related to early childhood science concepts, this is due to teachers who do not gain clear knowledge about science concepts. This article aims to provide understanding and mastery related to science concepts for early childhood, so as to reduce the occurrence of misconceptions or concepts that are not in accordance with scientific understanding